UMUMTA’LIM MAKTAB DIREKTORLARIDA TAYM-MENEJMENT KO‘NIKMALARINI RIVOJLANTIRISh: NAZARIYADAN AMALIYOTGA - Bekniyazov, B.S. (SCIENCE and SOCIETY, 2025)
The article discusses the functional tasks of modern school leaders and the effectiveness of management activities, strategic management and planning in secondary schools, management algorithm, labor ethics in management, the manager’s working time and its use.